2022
DOI: 10.3389/fcimb.2022.788692
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Interferon-Gamma Release Assays for Tuberculous Meningitis: A Systematic Review and Meta-Analysis

Abstract: BackgroundIn this study, we evaluated and compared the accuracy of blood and cerebrospinal fluid (CSF) interferon release tests [interferon-gamma release assays (IGRAs)] in the diagnosis of tuberculous meningitis (TBM) by a meta-analysis of the relevant literature.MethodsWe searched for studies published before 2021 in Medline, Embase, the Cochrane database, and Chinese databases. All studies used the QuantiFERON-TB Gold In-Tube and/or T-SPOT.TB method. Blood and/or CSF tests that met the guidelines for the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Our review found that all patients tested positive for the CSF IGRA assay, underscoring its superior diagnostic e cacy. In comparison, a previous meta-analysis on CSF IGRAs in non-pregnant patients reported a pooled sensitivity of 79% (95% CI: 0.71-0.85) and a speci city of 95% (95% CI: 0.88-0.98), demonstrating its high diagnostic performance 53 . However, it is critical to note that blood samples must be processed within 8-30 hours post-collection for viability, and a positive result does not necessarily indicate active disease.…”
Section: Discussionmentioning
confidence: 76%
“…Our review found that all patients tested positive for the CSF IGRA assay, underscoring its superior diagnostic e cacy. In comparison, a previous meta-analysis on CSF IGRAs in non-pregnant patients reported a pooled sensitivity of 79% (95% CI: 0.71-0.85) and a speci city of 95% (95% CI: 0.88-0.98), demonstrating its high diagnostic performance 53 . However, it is critical to note that blood samples must be processed within 8-30 hours post-collection for viability, and a positive result does not necessarily indicate active disease.…”
Section: Discussionmentioning
confidence: 76%
“…Interferon-gamma release assays (IGRAs) are used to detect the presence of MTB infection by measuring the amount of interferon (IFN)-gamma released by T cells after stimulation with MTB-specific antigens and the number of T cells releasing IFN-gamma ( 44 ). A meta-analysis showed that the overall sensitivity and specificity of IGRA 74% and 79%, respectively, in blood, and 78% and 95%, respectively, in CSF, suggesting moderate accuracy in the diagnosis of TBM ( 35 , 36 ). However, IGRA is not effective at distinguishing between latent and active TB ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon gamma is mainly involved in immune regulation, and its expression level is associated with neurological diseases ( Zhang et al, 2020 ; Döhne et al, 2022 ; Wen et al, 2022 ). TBI could induce a serial of cytokines, including interferon gamma and activate various types of immune cells ( Siwicka-Gieroba and Dabrowski, 2021 ; Salem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%